Radiological classification of renal angiomyolipomas based on 127 tumors - Prando,Adilson (2003)
PURPOSE: Demonstrate radiological findings of 127 angiomyolipomas (AMLs) and propose a classification based on the radiological evidence of fat. MATERIALS AND METHODS: The imaging findings of 85 consecutive patients with AMLs: isolated (n = 73), multiple without tuberous sclerosis (TS) (n = 4) and multiple with TS (n = 8), were retrospectively reviewed. Eighteen AMLs (14%) presented with hemorrhage. All patients were submitted to a dedicated helical CT or magnetic resonance studies. All hemorrhagic and non-hemorrhagic lesions were grouped together since our objective was to analyze the presence of detectable fat. Out of 85 patients, 53 were monitored and 32 were treated surgically due to large perirenal component (n = 13), hemorrhage (n = 11) and impossibility of an adequate preoperative characterization (n = 8). There was not a case of renal cell carcinoma (RCC) with fat component in this group of patients. RESULTS: Based on the presence and amount of detectable fat within the lesion, AMLs were classified in 4 distinct radiological patterns: Pattern-I, predominantly fatty (usually less than 2 cm in diameter and intrarenal): 54%; Pattern-II, partially fatty (intrarenal or exophytic): 29%; Pattern-III, minimally fatty (most exophytic and perirenal): 11%; and Pattern-IV, without fat (most exophytic and perirenal): 6%. CONCLUSIONS: This proposed classification might be useful to understand the imaging manifestations of AMLs, their differential diagnosis and determine when further radiological evaluation would be necessary. Small (< 1.5 cm), pattern-I AMLs tend to be intra-renal, homogeneous and predominantly fatty. As they grow they tend to be partially or completely exophytic and heterogeneous (patterns II and III). The rare pattern-IV AMLs, however, can be small or large, intra-renal or exophytic but are always homogeneous and hyperdense mass. Since no renal cell carcinoma was found in our series, from an evidence-based practice, all renal mass with detectable fat should be considered an AML.